Evidence of artisanal fishing impacts and depth refuge in assemblages of Fijian reef fish - Goetze, J.; Langlois, T.; Egli, D.; Harvey, Euan (Springer Verlag, 2011)
Protection from fishing generally results in an increase in the abundance and biomass of species targeted by fisheries within marine reserve boundaries. Natural refuges such as depth may also protect such species, yet few studies in the Indo Pacific have investigated the effects of depth concomitant with marine reserves. We studied the effects of artisanal fishing and depth on reef fish assemblages in the Kubulau District of Vanua Levu Island, Fiji, using baited remote underwater stereo-video systems. Video samples were collected from shallow (5–8 m) and deep (25–30 m) sites inside and outside of a large old marine reserve (60.6 km2, 13 years old) and a small new marine reserve (4.25 km2, 4 years old). Species richness tended to be greater in the shallow waters of the large old reserve when compared to fished areas. In the deeper waters, species richness appeared to be comparable. The difference in shallow waters was driven by species targeted by fisheries, indicative of a depth refuge effect. In contrast, differences in the abundance composition of the fish assemblage existed between protected and fished areas for deep sites, but not shallow. Fish species targeted by local fisheries were 89% more abundant inside the large old reserve than surrounding fished areas, while non-targeted species were comparable. We observed no difference in the species richness or abundance of species targeted by fisheries inside and outside of the small new reserve. This study suggests that artisanal fishing impacts on the abundance and species richness of coral reef fish assemblages and effects of protection are more apparent with large reserves that have been established for a long period of time. Observed effects of protection also vary with depth, highlighting the importance of explicitly incorporating multiple depth strata in studies of marine reserves.